2019
DOI: 10.1001/jamanetworkopen.2019.9910
|View full text |Cite
|
Sign up to set email alerts
|

Association of Mental Health Disorders With Health Care Utilization and Costs Among Adults With Chronic Disease

Abstract: Key Points Question Are mental health disorders associated with health care utilization and costs among people with chronic diseases? Findings In this population-based cohort study of 991 445 Canadian adults, including 156 296 with a mental health disorder, 3-year adjusted mean costs were $38 250 for those with a mental health disorder and $22 280 for those without a mental health disorder. Presence of a mental health disorder was associated with higher rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
89
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(100 citation statements)
references
References 80 publications
7
89
1
3
Order By: Relevance
“…Table 2 describes the 30 studies (containing 38 separate analyses) that assessed the impact of SMI on nonpsychiatric LOS [ 17 , 18 , 20 , 28 30 , 32 , 40 42 , 46 65 ]. In 29 of the 38 analyses, SMI was associated with increased LOS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 describes the 30 studies (containing 38 separate analyses) that assessed the impact of SMI on nonpsychiatric LOS [ 17 , 18 , 20 , 28 30 , 32 , 40 42 , 46 65 ]. In 29 of the 38 analyses, SMI was associated with increased LOS.…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen studies (17 analyses) were potentially suitable for meta-analysis, as they reported the mean LOS (and standard deviation or CIs) for patients with and without SMI [ 20 , 28 , 30 , 41 , 42 , 46 , 48 , 51 , 54 , 56 , 58 , 59 , 61 , 62 , 65 ]. The Higgins’ I 2 indicated that the set of studies were extremely heterogeneous (χ 2 [ 16 ] = 15,432.12, p < 0.001, I 2 = 100%); therefore, the estimation of the overall pooled effect should be interpreted with caution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 43 However, our study population likely had some sort of mental health coverage, since 98% of individuals with an employer sponsored health plan had mental health coverage in 2009, prior to the Affordable Care Act which expanded behavioral health parity. 44 Our regression models could not properly control for overall healthcare service utilization, which is correlated with the presence of mental health disorders, 45 as healthcare utilization is a mediator between exposure and outcome in our study and could bias the results. Finally, our study population had some differing demographic characteristics than BLS data on private workers and IBI's benchmarking database, which indicates that future research is needed to confirm that the results presented in this study are generalizable to a population with different sociodemographic characteristics.…”
Section: Discussionmentioning
confidence: 93%